Porta entreaberta: a prostituição feminina enquanto trabalho e formação identitária - Carloni, André Ramos [UNESP] (2016)
In this work, we studied the topic of female prostitution with the mainstreaming of social relations of gender and identity constructions. In this way, it has that prostitution can be understood as the act of delivery of the body and sex to others in exchange for money, and thus, it became a "job", even if not officially recognized in Brazil, but that many are fighting for it. We can tell it's something that instigates a lot, but it can also state that is the subject of many. Within this scenario, we can see the female prostitution is a big business, both in the sense of scale, as in the sense of financial movement. And it is through this "job" that we can understand some social representations of women and their identity characteristics, recalling that the identity constructions are in a particular time and space, especially within the social relations of gender, in which the woman hasn't conquered effectively the level of equal right and opportunity to the man. In this way, we aim for find out the processes of identity formation in front of the notorious gender imbalance in the female prostitution, which as seen, it is not legally recognized as a profession. This research was accomplished with researches at the current time, that is, between 2013 and 2016. To this end, in addition to an extensive bibliographical research that addressed since books until recent and updated articles, there was the participation, through form of 01 prostitute, which had to contribute to the research. However, we have sent 18 forms to coordinators and Presidents of associations and NGOs, that represent prostitutes in several Brazilian States and 4 interview requests of the southeast region of Brazil. Finally, we searched secondary data as Web pages, movies, which have tackled the role of prostitute and online surveys of prostitutes. This research approach was qualitative, aiming at enabling the researcher an analytical critical reflection in the face of the daily life of prostitutes. So, in an analysis of the dialectical method, we gather data that subsidized analysis about the formatting of women identities in the prostitution.